Correlation between Serum Levels of High Mobility Group Box-1 Protein and Pancreatitis: A Meta-Analysis. (28th January 2015) - Lin, Yan; Lin, Lian-Jie; Jin, Yu; Cao, Yong; Zhang, Ying; Zheng, Chang-Qing; Liu, Jia-Li; Yang, Sheng-Li
Abstract : Background . Aberrant expression of high mobility group box-1 protein (HMGB1) contributes to the progression of various inflammatory diseases. This meta-analysis focused on the clinical significance of serum HMGB1 levels in pancreatitis patients, with the goal of building a novel diagnostic score model. Method . We conducted a meta-analysis by searching in the PubMed, Embase, Web of Science, Cochrane Library, CISCOM, CINAHL, Google Scholar, China BioMedicine (CBM), and China National Knowledge Infrastructure (CNKI) databases without any language restrictions. Studies were pooled and standard mean difference (SMD) and its corresponding 95% confidence intervals (95% CIs) were calculated. Version 12.0 STATA software was used for statistical analysis. Results . We performed a final analysis of 841 subjects from 12 clinical case-control studies. The meta-analysis results showed a positive association between serum HMGB1 levels and the progression of pancreatitis. In the subgroup analysis by country, high serum level of HMGB1 may be related to pancreatitis progression in China, Korea, Hungary, and Japan populations (all P < 0.05 ). Conclusion . The present meta-analysis indicated that serum HMGB1 level was statistically elevated in patients with pancreatitis, and thus serum levels of HMGB1 could be determined to be a useful biomarker for pancreatitis patients.